Effect of Different Pediatric Medications on RMGIC: A Comparative Study - Ahtesham A. Qurishi; Mohammed S. Al Dira; Amal H. Sholan; Shahad E. Abzoah; Mahdi A. Hakami; Emad Malhan; Shahad M. Moafa (Journal of Pharmacy and Bioallied Sciences)
Introduction: This study investigates the impact of commonly prescribed pediatric medications on resin-modified glass ionomer cement (RMGIC), which is widely used in pediatric dentistry in India. The interaction between these medications and RMGIC could affect the material’s durability and effectiveness. Methodology: Sixty RMGIC specimens were divided into five groups, each exposed to different pediatric medications: antibiotic syrup, antipyretic syrup, vitamin syrup, antitussive syrup, and distilled water (control). Microhardness and surface roughness were measured before and after a 14-day immersion period. Statistical analysis was conducted using one-way ANOVA and post-hoc Tukey’s test. Results: All pediatric medications significantly affected RMGIC, with antitussive syrup showing the most substantial impact. Microhardness decreased by up to 18.40%, and surface roughness increased by up to 21.40%. The control group showed no significant changes. Conclusion: Pediatric medications, particularly those with acidic properties, compromise the durability of RMGIC. Further research is needed to develop more resistant materials or protective measures.